Treatment of Hyperlactatemia in Acute Circulatory Failure Based on CO2-O2-Derived Indices: Study Protocol for a Prospective, Multicentric, Single, Blind, Randomized, Superiority Study (The LACTEL Study) - Caruso, Vincenza; Besch, Guillaume; Nguyen, Maxime; Pili-Floury, Sebastien; Bouhemad, Belaid; Guinot, Pierre-Grégoire; , the Lactel Study Group; Martin, Audrey; Radhouani, Mohamed; Constandache, Tiberiu; Grosjean, Sandrine; Voizeux, Pierre; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Hyperlactatemia is a biological marker of tissue hypoperfusion with well-known diagnostic, prognostic, and therapeutic implications in shock states. In daily clinical practice, it is difficult to find out the exact mechanism underlying hyperlactatemia. Central venous to arterial CO2 difference (pCO2 gap) is a better parameter of tissue hypoperfusion than the usual ones (clinical examination and mixed venous saturation). Furthermore, the ratio between the pCO2 gap and p(v–a)CO2/C(a–v)O2 may be a promising indicator of anaerobic metabolism, allowing for the identification of different causes of tissue hypoxia and hyperlactatemia. The main aim of the study is to demonstrate that initial hemodynamic resuscitation based on an algorithm integrating the pCO2 gap and p(v–a)CO2/C(a–v)O2 ratio vs. usual clinical practice in acute circulatory failure improves lactate clearance. Methods LACTEL is a randomized, prospective, multicentric, controlled study. It compares the treatment of hyperlactatemia using an algorithm based on the pCO2 gap and P(v–a)CO2/C(a–v)O2 ratio vs. usual clinical practice in acute circulatory failure. A total of 90 patients were enrolled in each treatment group. The primary endpoint is the number of patients with a lactate clearance of more than 10% 2 h after inclusion. Lactate levels were monitored during the first 48 h of treatment as hemodynamic parameters, biological markers of organ failure, and 28-day mortality. Discussion pCO2 derivate indices may be of better interest than routine clinical indices to differentiate causes of hyperlactatemia and diagnose anaerobiosis. LACTEL results will provide clinical insights into the role of these indices in the early hemodynamic management of acute circulatory failure in the ICU. Clinical Trial Registration www.clinicaltrials.gov; identifier: NCT05032521.